A Triplet Track Trigger for the FCC-hh to improve the measurement of Di-Higgs production and the Higgs self-coupling - Kar, Tamasi Rameshchandra; Schöning, André (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2024)
A new concept, the Triplet Track Trigger (TTT), is proposed for stand-alone tracking at the first trigger level of an FCC-hh detector. The concept is based on a highly scalable monolithic pixel sensor technology and uses a very simple and fast track reconstruction algorithm that can be easily implemented in hardware processors. The goal is to suppress the enormous pileup of ∼1000 minimum bias collisions expected at the FCC-hh experiments and to identify the hard-interaction vertex and the corresponding tracks as a basis for a trigger decision. In the barrel region, the TTT consists of three closely stacked, highly granular pixel detector layers at radii of ∼1m. An extension of the TTT to the endcap region increases the geometrical acceptance. We present full Geant4 simulations and reconstruction performance of a modified FCC-hh reference tracker that includes TTT barrel and endcap detector layers. The stacking of TTT layers results in excellent track purity, and the large lever arm ensures very good momentum resolution. Additionally, sub-mm z vertex resolution is achieved, which allows for very efficient pileup suppression. By reconstructing pileup suppressed track-jets, the primary vertex of the hard interaction is successfully identified, even at a pileup rate of 〈μ〉=1000 and at trigger level. The multi-jet signature, pp→HH→bb¯bb¯ is used as a showcase to study the trigger performance of the TTT and compare it to an emulated calorimeter trigger (calo-trigger). The TTT allows for significantly lower trigger thresholds and higher trigger efficiencies compared to a calo-trigger. Furthermore, the TTT is very robust against fluctuations in the pileup rate in contrast to the calo-trigger. As a result, a significant increase in the statistics of di-Higgs events is expected, in particular at low transverse momentum, where the sensitivity to the trilinear Higgs self-coupling (λ) is the highest.
Gesehen am 25.08.2025